2018
DOI: 10.1177/0030222818819340
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Living Inventory for Adolescents: Psychometric Properties Among Portuguese Adolescents

Abstract: Reasons for living are protective factors against suicidal behavior in adolescents. One of the most useful measures to assess them is the Reasons for Living Inventory for Adolescents (RFL-A) developed by Osman et al. The goal of this study was to examine the psychometric properties of its Portuguese version of the RFL-A. To this end, we recruited 512 high school adolescents (mean age = 16.7 years), who completed the RFL-A, a Suicidal Ideation Questionnaire, and a hopelessness scale. Exploratory factor analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…All the GOF indices in the 4-factor model matched the parameters estimated in the literature. Although the original study (Pirani et al, 2021) partially supported the 1-factor model, this study and other studies on students (Gutierrez et al, 2002;Westefeld et al, 1992) and even adolescents (Ventosa Brás et al, 2021) reported stronger evidence for the 4-factor model. Overall, the values of the factor loads and the correlations between them (Table 4) confirmed the superiority of the 4-factor model to the 1-factor model.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…All the GOF indices in the 4-factor model matched the parameters estimated in the literature. Although the original study (Pirani et al, 2021) partially supported the 1-factor model, this study and other studies on students (Gutierrez et al, 2002;Westefeld et al, 1992) and even adolescents (Ventosa Brás et al, 2021) reported stronger evidence for the 4-factor model. Overall, the values of the factor loads and the correlations between them (Table 4) confirmed the superiority of the 4-factor model to the 1-factor model.…”
Section: Discussioncontrasting
confidence: 63%
“…The pervasiveness and increase in suicidal ideation and attempts among young people and students have been among the concerns of researchers and mental health care professionals. Accordingly, several studies in recent decades have been dedicated to investigating suicide in young adults with special attention to the risk factors (Ventosa Brás, et al, 2021). However, researchers have concluded that protective factors can considerably prevent suicidal ideation and behavior (Gutierrez, et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicate more frequent and pervasive SI; a cut-off of 41 is typically used to indicate heightened suicidal risk (Reynolds, 1988). The SIQ exhibits high internal consistency (Cronbach’s α ⩾ 0.95; Gutierrez and Osman, 2009; Jia et al, 2014; Reynolds, 1988; Ventosa Brás et al, 2021) and acceptable test–retest reliability over a 4-week interval (0.72; Reynolds, 1988) and over a 12-week interval in this study (intraclass correlation coefficient [ICC] = 0.73) based on a single rater, consistency, two-way mixed-effects model (Koo and Li, 2016). Construct and concurrent validity are well established (Abdel-Khalek and Lester, 2007; Cassady and Cross, 2006; Erford et al, 2018; Jia et al, 2014; Potard et al, 2014; Reynolds, 1988; Zhang et al, 2014).…”
Section: Methodsmentioning
confidence: 73%
“…The RFL-A score is obtained by averaging the items, with high scores suggesting more reasons for living [ 12 ]. Subdivided into five factors, the scale exhibits satisfactory reliability in the original study (total scale: α=0.96; family alliance: α=0.94; suicide-related concerns: α=0.93; peer acceptance and support: α=0.89; future optimism: α=0.92; and self-acceptance: α=0.94) [ 12 ], in the Portuguese study (total scale: α=0.94; family alliance: α=0.95; suicide-related concerns: α=0.87; peer acceptance and support: α=0.89; future optimism: α=0.85; and self-acceptance: α=0.91), [ 26 ] and in the present study (total scale: α=0.97; family alliance: α=0.94; suicide-related concerns: α=0.91; peer acceptance and support: α=0.92; future optimism: α=0.93; and self-acceptance: α=0.94).…”
Section: Methodsmentioning
confidence: 99%